1971
DOI: 10.1042/bj1220115
|View full text |Cite
|
Sign up to set email alerts
|

The role of adenosine 3′:5′-cyclic monophosphate in the regulation of insulin release by isolated rat islets of Langerhans

Abstract: 1. Concentrations of cyclic AMP (adenosine 3':5'-cyclic monophosphate) and rates of insulin release were measured in islets of Langerhans isolated from rat pancreas and incubated for various times in the presence of glucose, 3-isobutyl-1-methylxanthine, caffeine, theophylline, adrenaline and diazoxide. 2. Caffeine and theophylline produced small but significant increases in both cyclic AMP and release of insulin when they were incubated in the presence of 10mm-glucose. 3. 3-Isobutyl-1-methylxanthine produced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
89
1
1

Year Published

1972
1972
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(98 citation statements)
references
References 19 publications
7
89
1
1
Order By: Relevance
“…Experiments with theophylline, which elevates islet cyclic AMP levels by inhibiting cyclic nucleotide phosphodiesterase [18], did not produce any evidence that the generation of cyclic AMP can induce a primed state in the B cell. Others [13] have shown that the enhanced secretion of insulin which occurs after glucose priming is not accompanied by a simultaneous increase in islet cyclic AMP formation.…”
Section: Discussionmentioning
confidence: 84%
“…Experiments with theophylline, which elevates islet cyclic AMP levels by inhibiting cyclic nucleotide phosphodiesterase [18], did not produce any evidence that the generation of cyclic AMP can induce a primed state in the B cell. Others [13] have shown that the enhanced secretion of insulin which occurs after glucose priming is not accompanied by a simultaneous increase in islet cyclic AMP formation.…”
Section: Discussionmentioning
confidence: 84%
“…Ultrasonication of the incubate was followed by a centrifugation step, when acid-precipitated protein was spun down. Supernatants were chromatographed on Dowex 50 [8], lyophilised, and then dissolved in Tris buffer (50 mM; pH 7.4). Samples were taken for estimation of loss of cyclic AMP during the purification procedure.…”
Section: Methodsmentioning
confidence: 99%
“…First, glycogen accumulates in B-cells exposed for a sufficient time to high concentrations of glucose (Lazarow, 1963). Secondly, theophylline is known to increase the concentration of cyclic AMP in pancreatic endocrine cells (Charles et al, 1973;Montague & Cook, 1971;Turtle & Kipnis, 1967) and, in turn, cyclic AMP is reported to stimulate glycogenolysis in islet tissue (Hellman & Idahl, 1970).…”
Section: Discussionmentioning
confidence: 99%